(untitled) (Journal of Information Technologies in Education (ITE), 2009)
The article analyzes modern learning materials (MLM) creation problems and the existing tools for such materials creation, their weaknesses and suggests ways to address them. Creation of new complex is proposed, which will support (creation, collecting and displaying) several types of MYM, templates, interactive elements, which can show the dynamic processes, as well as support for MLM bank with searching, sorting, and grouping capabilities.